Solve for z p=5g+5z

Math
p=5g+5z
Rewrite the equation as 5g+5z=p.
5g+5z=p
Subtract 5g from both sides of the equation.
5z=p-5g
Divide each term by 5 and simplify.
Tap for more steps…
Divide each term in 5z=p-5g by 5.
5z5=p5+-5g5
Cancel the common factor of 5.
Tap for more steps…
Cancel the common factor.
5z5=p5+-5g5
Divide z by 1.
z=p5+-5g5
z=p5+-5g5
Cancel the common factor of -5 and 5.
Tap for more steps…
Factor 5 out of -5g.
z=p5+5(-g)5
Cancel the common factors.
Tap for more steps…
Factor 5 out of 5.
z=p5+5(-g)5(1)
Cancel the common factor.
z=p5+5(-g)5⋅1
Rewrite the expression.
z=p5+-g1
Divide -g by 1.
z=p5-g
z=p5-g
z=p5-g
z=p5-g
Solve for z p=5g+5z

Solving MATH problems

We can solve all math problems. Get help on the web or with our math app

Scroll to top